PERENCANAAN SISTEM HYBRID PHOTOVOLTAIC DAN PLN DI UNIVERSITAS BANGKA BELITUNG - Muhammad Ali Raja Siregar; Wahri Sunanda; Ghiri Basuki Putra (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2019)
Electricity at Universitas Bangka Belitung is currently supplied by the Bangka Belitung Region PLN with a power supply of 690 kVA to meet electrical energy needs. This study analyzes the hybrid photovoltaic-PLN pattern in UBB to find out more economical systems. The calculation result of the more economical hybrid pattern is the pattern with the distribution of PLN's load of 70% -30% PLTS which results in a Net Present Cost (NPC) value of US $ 1,071 M and a Cost Of Energy (COE) of US $ 0.107.